Surgical evacuation of the stomach in the treatment of massive intoxications by psychotropic drugs - Artucio, Hernán; Panizza, Rodolfo; Wolyivovics, Mendel; Mazza de Prato, Norma; Correa, Humberto; Caritat, Ricardo; Muchada, Raúl; González, Tabaré; Pulido, Angelica; Cazabán, Luis A; Matteucci, Pablo; Fernández, Gonzalo J (Cirugía del Uruguay, 1974)
A series of 10 patients with massive drug intoxication was solved by surgical dumping of stomach. Gastrostomy performed before 18 hours had shortened evolution and added no complications. Surgical technique consisted of transversal corporal gastrostomy, lavage and aspiration of contents, specially trose of fundus, and closure in two planes; Foley's probe is left in gastrostomy.